Federal-State regulation of the pricing and marketing of insurance - United States; Maseritz, Guy B.; MacAvoy, Paul W.; United States (Washington : American Enterprise Institute for Public Policy Research, 1977)
Originally prepared as a working paper by the Antitrust Division of the Dept. of Justice. Cf. U.S. Task Group on Antitrust Immunities. Report. "[Prepared in connection with a study conducted] at the request of the Task Force [i.e. Group] on Antitrust Immunities."
Includes bibliographical references.
aia 02/04/2019
Loans
Keywords: Insurance; Insurance companies; Insurance